To Teach Higher Education Students How to use the Teacher-Student Relationship in Teaching the Younger Generation - Xojiyeva Zamiraxon Quchqarovna (Researchparks Publishing, 2021)
Today, in our place, which has a unique experience in training qualified, educated personnel, we must work hard to educate students in science and enlightenment, to train them as modern personnel in teaching. At a time when the innovations of science and technology of the XXI century are rapidly coming to life in the higher education system of Uzbekistan, innovations are taking place in the field of education. Curricula are being improved in all areas of education, including music education, and a new generation of literature is being created. This article discusses how to teach higher education students how to use teacher-student relationships in vocational guidance for the younger generation.